A carbon nanotube based ion source for planetary space mass spectrometry - Steichen, Valentin; Leblanc, François; Berthelier, Jean Jacques; Hong, Nguyen Tuan; Lee, Soonil; Gilbert, Pierre (Review of Scientific Instruments, 2024)
Ion sources are used in mass and energy spectrometry to ionize the neutral particles entering the instrument. The most classical technique used in planetary exploration is hot filaments emitting electrons with few tens of eV and impacting the neutral particles. The main limitations of such emitters are power consumption and outgassing due to heating of their local environment. Here, we built, tested, and demonstrated the advantages of using carbon nanotubes to replace hot filaments. Such emitters are based on a cold approach, use a limited amount of power, and achieve essentially the same efficiency as the hot filament-based source of ionization.
Keywords: A-carbon; Classical techniques; Energy; Hot-filament; Local environments; Neutral particles; Planetary exploration; Power